New insights into the rapid formation of initial membrane fouling after in-situ cleaning in a membrane bioreactor. (March 2019) - Sun, Ming; Yan, Linlin; Zhang, Lanhe; Song, Lianfa; Guo, Jingbo; Zhang, Haifeng
Graphical abstract: Highlights: The sludge after in-situ cleaning promotes the rapid formation of initial fouling. The sludge after in-situ cleaning had a high protein content in the EPS layers. The sludge after in-situ cleaning had higher adhesive and cohesive abilities. Abstract: In-situ chemical cleaning with sodium hypochlorite (NaClO) is often employed for maintaining constant permeability in a membrane bioreactor (MBR). In this study, the effect of NaClO shock on the rapid formation of initial membrane fouling was investigated over the course of the in-situ cleaning of a MBR. Variations of trans-membrane pressure (TMP) in the different runs indicated that the bulk sludge after NaClO-shock promotes the rapid formation of initial membrane fouling. After in-situ cleaning, the sludge had a high protein content in different extracellular polymeric substance layers and a substantial deterioration in sludge filterability compared to raw sludge. Based on the extended Derjaguin-Landau-Verwey-Overbeek (XDLVO) theory, NaClO shock significantly changes the surface properties of raw sludge. It reduces the surface electron donor component ( γ − ) and increases surface hydrophobicity. The sludge after NaClO-shock exhibited a stronger adhesive energy with the membrane and higher self-cohesive ability, resulting in severe membrane fouling.